ALGEBRA 1!PLZ HELP!

posted by .

Use the Substitution method to solve the system of equations.

y - 2x = -5
3y - x = 5

Solve the first equation for y.
y = 2x-5
Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back into the first equation and solve for y. Post your work if you get stuck.

WOULD IT BE:
4Y-X=0?

y - 2x = -5 (equation 1)
3y - x = 5 (equation 2)
=============
Use equation 1 to solve for y as I did earlier.
y = 2x + 5
Now substitute that value of y (from equation 1) into equation 2.
equation 2 is
3y-x=5. Plug the value for y into this.
3(2x+5)-x=5
Now solve for x. Then use that value for x into equation 1 and solve for y.
Post your work if you get stuck. Not a "would it be" answer.

what is a possible point that lies on the graph

y=-2x-5


yo mama

  • ALGEBRA 1!PLZ HELP! -

    well. im failing algebra jus as u r probably if ur askin help online from random ppl. sorry i cant help.

  • ALGEBRA 1!PLZ HELP! -

    Wrong

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Substitution Method

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 x + y = -4 x - y = 2 In the second equation, x= y+2 Putting that in the first.. (y+2) + y= -4 subtract two from each side, then divide each side by …
  2. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  3. Algebra 1 HELP PLZ!!!

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 PLz HELP!! I'M NOT BOB BUT I CAN HELP ITS REALLY SIMPLE ALGEBRA X + Y = -4......EQN 1 X - Y = 2.....EQN 2 From EQN 2, let x = 2 + y Substitute that …
  4. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second equation …
  5. substitution method

    -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y = -14 2x = y + 1 Let's solve the second equation for y: y = 2x - 1 Now let's substitute (2x - 1) for y in the first equation: -x - 4(2x - 1) = -14 -x - 8x + 4 = -14 -9x + 4 …
  6. substitution method

    -3x+y=-5 x+2y=0 Your equations: -3x + y = -5 x + 2y = 0 Let's solve the second equation for x: x = -2y Now let's substitute -2y for x in the first equation to solve for y: -3(-2y) + y = -5 6y + y = -5 7y = -5 y = -5/7 Now let's substitute …
  7. Alg-Substitution (check plz)

    k well i had to use substitution to find the point of intersection for these 2 equations x-y=10 3x+y=11 i chose to substitute y in the first equation my final answer was (-1/2 , 5) can someone clarify this, and if it's wrong, where'd …
  8. algebra

    5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first equation, then solve it for x. Substitute 5x +3 for y in the first equation, then solve it for x. When I subsitute 5x+3 into the equation I get x=1/5 and y=2 is this …
  9. subsitution method

    Can some one show me how to use the Substitution method to solve the system of these equations. x + y = -4 x - y = 2 x + y = 10 y = x + 8 on the first set. Solve for either x or y in either equation, then put that value into the other …
  10. Algebra 1

    What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ?

More Similar Questions